Experimental analysis of multistatic multiband radar signatures of wind turbines. Issue 8 (1st October 2016) - Fioranelli, Francesco; Ritchie, Matthew; Balleri, Alessio; Griffiths, Hugh
Abstract : This study presents the analysis of recent experimental data acquired using two radar systems at S‐band and X‐band to measure simultaneous monostatic and bistatic signatures of operational wind turbines near Shrivenham, UK. Bistatic and multistatic radars are a potential approach to mitigate the adverse effects of wind farm clutter on the performance of radar systems, which is a well‐known problem for air traffic control and air defence radar. This analysis compares the simultaneous monostatic and bistatic micro‐Doppler signatures of two operational turbines and investigates the key differences at bistatic angles up to 23°. The variations of the signature with different polarisations, namely vertical transmitted and vertical received and horizontal transmitted and horizontal received, are also discussed.